Impact of lactate on 30-day all-cause mortality in patients with and without out-of-hospital cardiac arrest due to cardiogenic shock - Rusnak, Jonas; Schupp, Tobias; Weidner, Kathrin; Ruka, Marinela; Egner-Walter, Sascha; Forner, Jan; Bertsch, Thomas; Kittel, Maximilian; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Behnes, Michael; et al. (Journal of Clinical Medicine, 2022)
In patients with cardiogenic shock (CS) due to myocardial infarction, elevated lactate levels are known to be negative predictors. Studies regarding the prognostic impact in patients with CS complicated by out-of-hospital cardiac arrest (OHCA) are limited. Two hundred and sixty-three consecutive patients with CS were included. The prognostic value of lactate on days 1, 2, 3, 4 and 8 was tested stratified by OHCA and non-OHCA. Statistical analyses included the univariable t-test, Spearman’s correlation, C-statistics, Kaplan-Meier analyses, as well as multivariable mixed analysis of variance (ANOVA) and Cox proportional regression analyses. The primary endpoint of all-cause mortality occurred in 49.4% of the non-OHCA group and in 63.4% of the OHCA group. Multivariable regression models showed an association of lactate values with 30-day all-cause mortality in the non-OHCA (p = 0.024) and OHCA groups (p = 0.001). In Kaplan-Meier analyses, patients with lactate levels ≥ 4 mmol/L (log-rank p = 0.001) showed the highest risk for 30-day all-cause mortality in the non-OHCA as well as in the OHCA group. However, in C-statistics lactate on days 1 and 8 had a better discrimination for 30-day all-cause mortality in the OHCA group compared to the non-OHCA group. In conclusion, patients presenting with CS lactate levels showed a good prognostic performance, with and without OHCA. Especially, lactate levels on days 1 and 8 were more accurate in the discrimination for all-cause mortality in CS-patients with OHCA.
Gesehen am 26.06.2023